Seni Pertunjukan Topeng Tradisional di Surakarta dan Yogyakarta - R.M. Pramutomo (Universitas Gadjah Mada, 2014)
This article examine a study of exploration in which is ‘style’ of masked dancedrama’sconcentration of Surakarta and Yogyakarta regions. Two of them were the center ofmasked dancedrama called ‘Dramatari Topeng’ in Java island. Because of the specifi cscope of study focussed on masked dancedrama in Java, so that the article will strivesa very limited topic namely ‘identifi cation of performance style’. Basic stuff of maskeddancedrama in Java based on movement materials of two different grand style inSurakarta include its root in Klaten and arround, and Yogyakarta style and its rootarround Kalasan area. All of two grand styles will explore using ethnochoreopogicalapproach which are combined by comparative study related to its urgence on multilayeredentities of their performance each other. Through this article we would recognize theaspects of identifi cation of grand style within two movement materials of the mostinfl uence dance style in the masked dancedrama in Java.